Preparation of a recyclable novel thermoresponsive affinity copolymer and its application towards ε-polylysine purification. (January 2020) - Yang, Fuhao; Wan, Junfen; Cao, Xuejun
Graphical abstract: Highlights: The lower critical solution temperature(LCST) of affinity copolymer was about 34.0 ℃, and its recovery reached over 95.0%. Adsorption mechanism have been studied using Langmuir and Freundlich model. The adsorption capacity of ε-polylysine reached 42.9 mg/g. The purity of ε-polylysine increased from 84% to 99%. Abstract: Thermo-responsive polymers have great potential for industrial applications of bio-separation and purification. However, the poor affinity and low recovery of thermoresponsive copolymers are the main factors limiting their large-scale application. In this paper, a recyclable thermoresponsive affinity copolymer (PNHM -IDA-Ni 2+ ) was prepared by immobilizing nickel ions (Ni 2+ ) on copolymer PNHM, and PNHM -IDA-Ni 2+ was applied to the purification of ε-polylysine. The lower critical solution temperature (LCST) of PNHM and PNHM -IDA-Ni 2+ were 31.0 °C and 34.0 °C, respectively. Additionally, the recoveries of both copolymers were over 95.0%. The main parameters, such as pH were investigated to optimize the adsorption conditions. In addition, the Langmuir and Freundlich adsorption models were used to predict the maximum adsorption capacity of ε-polylysine. The results of the affinity precipitation demonstrated that the maximum adsorption capacity was 42.9 mg/g, and the adsorption was considered to follow the mono-layer model. The thermodynamic parameters (ΔG 0, ΔH 0 and ΔS 0 ) of the ε-polylysine adsorption indicated that the adsorption was spontaneous and exothermic. The maximum elution recovery (93.5%) was achieved at pH 5.0 with 0.2 M imidazole. The results of tricine-SDS-PAGE and HPLC (Purity: increased from 84% to 99%) showed that the ε-polylysine was well separated from the crude extract by using the affinity copolymer PNHM -IDA-Ni 2+ .